A pilot study to validate AMTAS in a specialist outpatient clinic at a public restructured hospital in Singapore - Hazel Yeo Kai Hui; Kenneth Chua Wei De; Savitha Hosangadi Kamath; Steven Lock Hey Lee (Proceedings of Singapore Healthcare, 2023)
Background The prevalence of age-related hearing loss is expected to increase with the ageing population in Singapore resulting in increased demand for pure tone audiometry (PTA). One way of meeting the increased demand for PTA is the Automated Method of Testing Auditory Sensitivity (AMTAS). Nonetheless, before AMTAS may be implemented, it is important to validate its results by comparing them against those of conventional PTA for the diverse Singaporean population. Methods 100 participants were recruited from the Otorhinolaryngology clinic at a public hospital. PTA was conducted for participants via the conventional method and AMTAS. The hearing thresholds obtained via the two methods were then compared. A feedback questionnaire on the use of AMTAS was also completed by all participants. Results Air and bone conduction threshold results from 80 participants were analysed. The absolute mean difference in air conduction thresholds obtained via the two methods ranged from 3.30 to 9.62 dB. The absolute mean difference in bone conduction thresholds obtained via the two methods ranged from 8.16 to 9.38 dB. Most participants indicated that the machine was easy to use. Other feedback collected indicated that the AMTAS testing environment was noisy and that testing was fast. Conclusion This study finds that despite differences in hearing thresholds obtained via AMTAS and manual PTA, these differences are within the acceptable 10 dB test-retest variation. Nonetheless, existing issues related to the AMTAS software and noise levels in the testing environment will need to be addressed before it can be used in the clinic.